STRENGTH CALCULATION AND STRESS TEST OF THE IN-SERVICE BOX CRANE FOR FLOATING PRODUCTION STORAGE AND OFFLOADING - ZHOU Hong; YAN TingJun; ZHANG Gang (Jixie qiangdu)
Due to long-term used in the harsh environment,the functional degradation of the FPSO crane such as corrosion,fatigue crack,local failure occurred. The functional degradation could affect the normal use of the FPSO crane. According to the actual surveying data,the finite element model of the FPSO crane has been established by finite element software Ansys. The stress of high stress area has been tested according to the stress distribution of the FPSO crane. The calculation results of Ansys have been compared with the test data. The errors between calculation results and test data are in 14%,except of point 1941.The stress value of the most dangerous area is 247. 96 MPa,which is less than the allowable stress of the crane. Thus the strength requirement is satisfied. The relation between stress of key area of crane and the angle β of lifting has been analyzed. When the weight of lifting is close to the maximum working load,the working condition of β > 15°is preferred.